2010
DOI: 10.1007/s00044-010-9483-2
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antidyslipidemic activities of Cuminum cyminum L. in validated animal models

Abstract: The ethanolic extract of seeds of Cuminum cyminum (C.c) was found to improve glucose tolerance to the tune of around 18.3% (P \ 0.01) in normal rats and shows around 17.7% (P \ 0.01) and 17.1% fall on blood glucose levels at 0-300 and 0-1440 min, respectively, on streptozotocin-induced diabetic rats at an oral dose of 250 mg/Kg body weight. The extract has also been found to improve around 26.7% (P \ 0.01) glucose intolerance on 14th day post treatment in high fructose fed streptozotocininduced diabetic rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Deleterious impact of oxidative stress in biological systems is related to the damage of proteins, enzymes 20 and various transcriptional factors like NFkB and AP-1 21 . Oxidation of the sulphydryl groups of cysteine to cystine may cause changes in the structure and functions of the proteins.…”
Section: Inhibition Of Copper Induced Protein Oxidative Modificationmentioning
confidence: 99%
“…Deleterious impact of oxidative stress in biological systems is related to the damage of proteins, enzymes 20 and various transcriptional factors like NFkB and AP-1 21 . Oxidation of the sulphydryl groups of cysteine to cystine may cause changes in the structure and functions of the proteins.…”
Section: Inhibition Of Copper Induced Protein Oxidative Modificationmentioning
confidence: 99%
“…Cuminaldehyde, the major component in green cumin, has inhibitory effects on carbohydrate digestion enzymes including a-glycosidase and adlose reductase (Srivsatava et al, 2011) and is identified as potent insulinotrophic and β-cell protective component (Patil, Takalikar, Joglekar, Haldavnekar, & Arvindekar, 2013).…”
Section: Abbreviationsmentioning
confidence: 99%
“…Blood glucose profile of each rat was determined just prior to the administration of test sample (-30 min), sucrose (0 min) and thereafter at 30, 60, 90 and 120 min post administration of sucrose by the glucometer. Food but not water was withdrawn from the cages during the course of experimentation 16 . Quantitative inhibition on the rise of postprandial hyperglycaemia post sucrose load by the test sample was calculated by plotting duration and blood glucose level on the x-and y-axis respectively.…”
Section: In Vivo Antihyperglycaemic and Antidyslipidaemic Activity Evmentioning
confidence: 99%
“…The biological studies of compound 3 and its enantiomers are presented here. The enantiomers of compound 3 have been obtained by asymmetric synthesis with optically pure epichlorohydrins following the protocol used earlier for atenolol, a -blocker drug 16 . In the method, hydroxyl-chalcone (6) obtained by the condensation of 4-hydroxy-acetophenone (4) and piperonal (5) was heated at ~100-120C with either R-or S-epichlorohydrin to give chlorohydrin intermediates 7a or 7b (Scheme 1), which were then cyclized in situ under basic conditions (aq.…”
Section: Synthesis Of Compound 3 and Its Enantiomersmentioning
confidence: 99%